Establishment and characterization of TRI-LC21: a novel patient-derived cell line of SMARCA4-deficient undifferentiated thoracic tumor - Shasha Li; Hao Luo; Dongsheng Wu; Yin Ku; Nanzhi Luo; Zhipeng Gong; Wenjing Zhou; Xinyi Xie; Guanyu Zhou; Yaohui Chen; Lunxu Liu (Human Cell, 2026)
SMARCA4-deficient thoracic undifferentiated tumor is a rare and highly aggressive subtype of lung cancer defined in the 2021 World Health Organization classification. Its scarcity and highly undifferentiated histology limit the availability of representative in vitro models and hinder therapeutic development. In this study, we established a novel cell line, TRI-LC21, from the primary tumor of a patient with lung cancer showing pathological features consistent with this entity. TRI-LC21 exhibited stable proliferation, strong colony-forming ability, and robust tumorigenicity in subcutaneous xenograft models. Xenograft tumors recapitulated the histological features and immunophenotype of the original tumor. Cell line authenticity was confirmed by short tandem repeat profiling, and mycoplasma contamination was excluded. Whole-exome sequencing revealed SMARCA4 loss accompanied by co-mutations in TP53 , STK11 , RBM10 , and ARHGAP35 . Transcriptome analysis demonstrated decreased expression of epithelial-associated genes and increased expression of stemness- and plasticity-related programs, consistent with an undifferentiated phenotype. Collectively, TRI-LC21 faithfully recapitulates the histological, immunophenotypic, and molecular characteristics of this tumor type and provides a valuable in vitro model for mechanistic investigation and preclinical studies.